Developing The Aawl-Ps: Academic Word List For Physical Sciences - Almira Fidela Artha; Ifa Febriyanti Muhaningrum; Keyraku Iaquinta Di Sayyidina; Jurianto Jurianto; Erlita Rusnaningtias (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to develop the Academic Article Word List for Physical Sciences (AAWL-PS), a corpus-based academic vocabulary list specifically designed for texts in the physical sciences. The development of this word list was motivated by the need for a more targeted lexical resource that reflects the linguistic characteristics of scientific disciplines such as Chemistry, Engineering, Physics, Mathematics, and Computer Science. The corpus used in this study consisted of 366 Scopus-indexed journal articles from nine sub-disciplines in the physical sciences, comprising a total of 2,632,817 running words. The study employed a quantitative corpus-based approach using AntWordProfiler software to identify and analyze high-frequency academic vocabulary items. Strict criteria of frequency, range, and dispersion were applied to extract the most representative and pedagogically useful vocabulary items. As a result, 350 high-utility word families were identified and compiled into the AAWL-PS. Comparative lexical coverage analysis revealed that AAWL-PS provides higher coverage of physical sciences texts than both the Academic Word List (AWL) and the New Academic Word List (NAWL). Specifically, AAWL-PS achieved 11.74% coverage of the primary corpus, outperforming NAWL (10.47%) and AWL (9.75%) despite containing fewer word families. A secondary validation test using a separate corpus of 824,056 tokens further confirmed the effectiveness of AAWL-PS, showing equivalent percentage coverage to NAWL but with higher token frequency. These findings demonstrate the importance of discipline-specific academic vocabulary lists in supporting English for Academic Purposes (EAP) instruction. The AAWL-PS can serve as a practical lexical resource for improving vocabulary acquisition, reading comprehension, and academic writing skills among students, researchers, and educators in the physical sciences.